An independent tuning current-reuse Gm-C complex biquad with high linearity. (December 2020) - Xie, Zushuai; Wu, Jianhui
Abstract: An independent tuning current-reuse Gm-C complex biquad is presented in this paper. By introducing extra freedoms, the proposed complex biquad achieves both independent tuning capability and higher linearity which are two big challenges preventing the reported current-reuse Gm-C filter from practical application. The prototype biquad is fabricated in standard 65-nm CMOS and the core circuit occupies 0.0512 mm 2 . It consumes 0.072 mW under 1.2-V supply. Monte Carlo (MC) simulation shows the proposed biquad features more robustness to mismatch variation. The center frequency and bandwidth of the biquad are about 2 MHz and 1.2 MHz, respectively. Measurement results indicate IIP3 of −9.53 dBm with image rejection ratio (IRR) of 25.3 dB.